TEKNOLOGI PENGAWETAN BUAH TOMAT DENGAN METODE FREEZE DRYING - Pujihastuti, Isti (METANA, 2009)
Â  Abstract The laboratory equipments are important in elaboration of technologies in freeze drying, for research of the product quality, amelioration, moreover determination of transport properties. Our department has a laboratory vacuum freeze drying equipment. We can register all the data during the procedure. It's important to analyze this freeze drying procedure, because this is elementary for system designing. we have constructed the necessary measuring instruments, their arrangement. The automatitation of this process isn't a simple problem. The principal measured characteristics are mass of dried product, temperature of dried product layer, temperature of the heater, vacuum, freezing temperature. We can measure the dried product's weight by a load cell, with the necessary accuracy. Â  Kata kunci : freeze drying, tomato Â